2016
DOI: 10.1111/ggr.12118
|View full text |Cite
|
Sign up to set email alerts
|

KArMars: A Breadboard Model for In Situ Absolute Geochronology Based on the K–Ar Method Using UV‐Laser‐Induced Breakdown Spectroscopy and Quadrupole Mass Spectrometry

Abstract: We present a breadboard prototype to perform in situ dating applicable to planetary exploration. Based on the K-Ar dating method and using instruments inspired by flight-proven analytical components, 'KArMars' ablated a geological sample under high vacuum with a quadrupled ultraviolet (UV at 266 nm) Nd:YAG laser. During ablation, the K content of the target material was given by laserinduced breakdown spectroscopy and the released 40 Ar was measured with a quadrupole mass spectrometer. Because K was measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 45 publications
1
23
0
Order By: Relevance
“…The larger mineral size of TL‐18 could account for the different ablation efficiency of different mineral species. The observed sample mass is comparable with those reported by Cohen et al (~50 μg) and between those reported by Devismes et al (~14 μg) and Cho et al (~100 μg). The volume differences with the latter two studies can be attributed to pulse numbers (i.e., 500 in this study vs 300), spot diameters (i.e., 400 μm in this study vs 250 μm), different laser wavelengths (i.e., 1064 nm in this study vs 266 nm), different laser pulse energies (i.e., 30 mJ in this study vs 100 mJ), or the relative hardness of the materials, where softer rocks develop deeper and larger‐diameter pits for the same laser energy deposited …”
Section: Age Measurement Results and Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The larger mineral size of TL‐18 could account for the different ablation efficiency of different mineral species. The observed sample mass is comparable with those reported by Cohen et al (~50 μg) and between those reported by Devismes et al (~14 μg) and Cho et al (~100 μg). The volume differences with the latter two studies can be attributed to pulse numbers (i.e., 500 in this study vs 300), spot diameters (i.e., 400 μm in this study vs 250 μm), different laser wavelengths (i.e., 1064 nm in this study vs 266 nm), different laser pulse energies (i.e., 30 mJ in this study vs 100 mJ), or the relative hardness of the materials, where softer rocks develop deeper and larger‐diameter pits for the same laser energy deposited …”
Section: Age Measurement Results and Discussionsupporting
confidence: 91%
“…Our isochrons show a large spot‐to‐spot variation of K contents (Figure ), reflecting the samples' heterogeneity on the scale of the laser spot (three‐dimensional parabolic pit with a ~400 μm opening at the sample surface and the depth of ~400 μm). For example, the range of K 2 O is larger than ×27 (<1000 ppm–2.7 wt%) for TL‐18 and larger than ×7 (<1000–7000 ppm) for TO‐35, whereas a fine‐grained basalt showed the variation of a factor of 8 (0.29–2.33 wt%) in a previous study . These lines of evidence suggest that a K abundance range larger than a factor of 4, which is used by Bogard as an example of desirable K range, is possible for basaltic samples.…”
Section: Age Measurement Results and Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Several laboratories have developed breadboards that would provide multiple measurements on a single solid sample by measuring K and Ar using a combination of LIBS to measure parent K, and MS to measure daughter Ar (Cohen et al , 2014; Solé, 2014; Cho et al , 2016; Devismes et al , 2016; Cho and Cohen, 2018; Cattani et al , 2019). These LIBS-MS instruments completely release Ar from small pits by laser ablation (LA) rather than oven heating and admit the released gas to the MS.…”
Section: Improving the Absolute Chronology Of Marsmentioning
confidence: 99%